(untitled) (International Journal of Biology and Chemistry, 2018)
Chitosan-unithiol composite for the first time was synthesized by simple and short period procedure. The sorption process was carried out under static conditions at temperature 298 K and at pH=4.5. The concentration of ions of toxic metals before and after sorption was determined by the atomic absorption method. The removal characteristics such as the removal degree and equilibrium time of Cu2+, Pb2+ and Cr6+ were illustrated. The adsorption equilibrium for Cu2+ ions was best described by Langmuir model and for Pb2+ and Cr6+ ions by Freundlich model. It was found that adsorption of Cu2+ and Cr6+ by chitosan-unithiol followed first-order kinetics. Adsorption of Pb2+ was followed second-order kinetics. The sorption process was also investigated under co-presence of heavy metal ions. The obtained results indicate that the synthesized chitosan-unithiol composite is the effective sorbent for removing toxic metal ions.